2021
DOI: 10.1111/jfpp.15392
|View full text |Cite
|
Sign up to set email alerts
|

Using white spread and compound chocolate as phenolic compound delivering agent: A model study with black carrot extract

Abstract: People of all age groups widely consume confectionery products (Parker et al., 2006). The main motivation factor for consuming these products is a pleasure. For this reason, their taste, flavor, texture, and visual characteristics should be considered in optimization, reformulation, and process development studies, even in enhancing functional properties. Coloring agents are widely used to improve visual characteristics in confectionery. Some of these agents also have potentially positive effects on consumer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
(68 reference statements)
0
6
0
1
Order By: Relevance
“…Additionally, Martini et al [ 6 ] found that in vitro gastrointestinal digestion processes decreased the antioxidant properties of DCh without and with Sakura green tea and turmeric powder when analyzed by ABTS, FRAP, and F–C ( Table 4 ). In contrast, DPPH and TPC values of compound chocolate samples fortified with black carrot extract significantly increased after in vitro digestion ( Table 4 , [ 12 ]). Thus, these supplemented confectionery products were advantageous for delivering and transporting phenolic and other antioxidant compounds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Martini et al [ 6 ] found that in vitro gastrointestinal digestion processes decreased the antioxidant properties of DCh without and with Sakura green tea and turmeric powder when analyzed by ABTS, FRAP, and F–C ( Table 4 ). In contrast, DPPH and TPC values of compound chocolate samples fortified with black carrot extract significantly increased after in vitro digestion ( Table 4 , [ 12 ]). Thus, these supplemented confectionery products were advantageous for delivering and transporting phenolic and other antioxidant compounds.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the addition of various plant extracts such as red raspberry leaves [5], yellow tea [7], Sakura green tea, turmeric powder [6], black carrot [12], dried cranberries, and prunes [2] to DCh samples and chocolate products caused an increase in AC and TPC analyzed by DPPH, ABTS, FRAP, and F-C assays (Table 4). Unexpectedly, the DPPH, ABTS, and TPC results [3] for all chocolate pralines produced with the addition of either longan or lychee were significantly lower than the antioxidant properties of control samples (Table 4).…”
Section: Antioxidant Capacity and Total Phenol Content In Chocolates Before And After In Vitro Simulated Digestionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Bolenz & Glöde (2021), grape pomace concentrations as low as 3.5% can significantly increase the polyphenol content of milk chocolate, but a pre‐grinding should be performed to avoid any negative effect of pomace on sensory properties of product. Especially in recent years, various plant extracts (Lončarević et al ., 2018), pigments (Baycar et al ., 2021a, 2022; Genc Polat et al ., 2020), products (Godočiková et al ., 2021; Żyżelewicz et al ., 2021) were used in white chocolate formulation. Among the reasons for using white chocolate in these studies are those; (i) white chocolate is disadvantageous in terms of polyphenol content due to the absence of cocoa solids, (ii) flavour changes due to the use of these alternative ingredients are masked by the presence of cocoa solids and/or (iii) product development with innovative visual properties.…”
Section: Introductionmentioning
confidence: 99%